C4-T3 Replacement Laminoplasty and Microsurgical Resection of Ependymoma: 2-Dimensional Operative Video. Issue 4 (30th June 2021) - Nguyen, Vincent N; Motiwala, Mustafa; Ha, Larry; Boom, Alan D; Boop, Frederick A
Abstract: Spinal ependymomas are the most common intramedullary spinal cord tumors in adults. 1-4 They are benign histologically, and maximum safe surgical resection should be pursued with the goal of maintaining neurological integrity. 4 Spinal ependymoma resections have been described in the operative video literature, including those using techniques of laminoplasty to prevent postlaminectomy kyphosis. 1-3, 5 Defining the planes between tumor and normal spinal cord is critical to achieving safe maximum resection. 3 This video will illustrate the microsurgical techniques used in the resection of a large spinal cord ependymoma in a patient who presented with progressive lower extremity paraparesis and incontinence and was found to have a large intradural, intramedullary C4-T3 lesion with a rostral glial tumor cyst. The patient consented to surgical intervention. The patient was placed prone in MAYFIELD 3-point pin fixation (Integra LifeSciences, Plainsboro Township, New Jersey). Intraoperative neurophysiological electrodes were placed for somatosensory evoked potentials, motor evoked potentials, and D-wave monitoring of corticospinal tracts. 6, 7 C3-T4 replacement laminoplasties were performed. A midline dural incision spanning C4-T4 was made. A midline myelotomy preserving the pial venous plexus was performed with a 69 Beaver blade. 2 The attachments of the tumor to the normal white matter of the spinal cord were microsurgically defined, coagulated, and divided. Tumor debulking was performed with an ultrasonic aspirator. Once gross total resection was achieved, the pial edges of the spinal cord were reapproximated. The dura was closed in a watertight fashion. The patient recovered from surgery well with preservation of her motor function with a continued T7 sensory level.